TRANSITION ELEMENTS IN WATER-BEARING SILICATE GLASSES/MELTS. PART I. A HIGH-RESOLUTION AND ANHARMONIC ANALYSIS OF NI COORDINATION ENVIRONMENTS IN CRYSTALS, GLASSES, AND MELTS - Farges F.; Brown G.E.; Petit P.E.; Munoz M. (My University, 2001)
The local structural environment around Ni(II) in a series of crystalline model compounds and K-Ni-, Na-Ni-, and Ca-Ni-silicate glasses and melts has been evaluated by using high-resolution Ni K-edge XANES spectroscopy and anharmonic EXAFS data analysis. The glasses show NBO/T contents ranging from 0 (albitic composition) to 1 (alkali-disilicate composition) and Ni contents ranging from 40 ppm to 2 wt.%.The pre-edge feature for model compounds vary not only in normalized height as a function of Ni-coordination but also in position (by ~0.5 eV) as confirmed by ab initio XANES calculations. In addition, the pre-edge position is indirectly correlated with the average Ni-O distance. By using these correlations, Ni is predicted to be 4-coordinated, on average, in the potassic glasses, ~5-coordinated in the sodic glasses, and >5-coordinated in the calcic glasses. The EXAFS-derived distances and coordination numbers are consistent with these conclusions, with the average Ni-O distances ranging between 1.96 and 2.03(2) Α. In contrast, NiO4 units are dominant in the melts examined (Na-disilicate composition with 4000 ppm of Ni).Variation in NBO/T or in Ni concentration does not affect the local environment of Ni in these silicate glasses whereas the type of network modifier present in the glass (K vs. Na vs. Ca + Mg) does. This finding explains the overall good agreement between this study and a previous XAFS study on silicate glasses with higher Ni concentrations and less polymerization (Galoisy and Calas, 1993a). In Part 2 of this series, these new correlations between Ni K-pre-edge features and Ni coordination number are used to characterize Ni structural environments in sodium trisilicate and albitic glasses containing 2000 ppm of Ni and exposed to pressures up to 5 kbars with 0 to 8 wt.% water. These hydrated glasses show major changes in their crystal field spectra, which correspond to major changes in the local coordination environment of Ni as revealed by XAFS spectroscopy.